Multiculturalism without culture - Phillips, Anne 1950- (Princeton, New Jersey Princeton University Press, 2007)
"Public opinion in recent years has soured on multiculturalism, due in large part to fears of radical Islam. In Multiculturalism without Culture, Anne Phillips contends that critics misrepresent culture as the explanation of everything individuals from minority and non-Western groups do. She puts forward a defense of multiculturalism that dispenses with notions of culture, instead placing individuals themselves at its core." "Opponents of multiculturalism may think the argument against accommodating cultural difference is over and won, but they are wrong. Phillips believes multiculturalism still has an important role to play in achieving greater social equality. In this book, she offers a new way of addressing dilemmas of justice and equality in multiethnic, multicultural societies, intervening at this critical moment when so many Western countries are poised to abandon multiculturalism."--BOOK JACKET.
Keywords: Feminism; Multiculturalism; Culture conflict; Sex discrimination against women